2020
DOI: 10.1371/journal.pone.0244477
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical characteristics, household transmission, and lethality of severe acute respiratory syndrome coronavirus-2 infection among healthcare workers in Ontario, Canada

Abstract: Introduction Protecting healthcare workers (HCWs) from Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a priority to maintain a safe and functioning healthcare system. Our objective was to describe and compare the epidemiology, clinical characteristics, and lethality of SARS-CoV-2 infections among HCWs compared to non-HCWs. Methods Using reportable disease data at Public Health Ontario, we conducted a population-based cross-sectional study comparing demographic, exposure, and clinical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 15 publications
1
36
2
2
Order By: Relevance
“…19 Ontario reported a rate 5.5 times higher for HCWs compared with non-HCWs. 5 In Scotland, hospital HCWs had a 3.4 times higher prevalence of SARS-CoV-2 antibodies than age-and sex-matched controls of general population (14.5% vs 4.8%). 20 In Wuhan, the attack rates among HCWs were 5.4 times higher than among non-HCWs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…19 Ontario reported a rate 5.5 times higher for HCWs compared with non-HCWs. 5 In Scotland, hospital HCWs had a 3.4 times higher prevalence of SARS-CoV-2 antibodies than age-and sex-matched controls of general population (14.5% vs 4.8%). 20 In Wuhan, the attack rates among HCWs were 5.4 times higher than among non-HCWs.…”
Section: Discussionmentioning
confidence: 92%
“…This rate is higher than the 17% pooled estimation from a recent meta-analysis of published studies in which secondary attack rates in households varied between 4% and 36%. 5 Patient-facing staff, mostly nurses and physicians, have been identified as occupations at highest risk, but most of these studies were hospital based. 12,13,[22][23][24] In our study, 35% of all infected HCWs were healthcare support workers (51% in LTCFs), 23% were nurses, 12% were nurse assistants, and 45% worked in LTCFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 The Toronto-based analysis cited previously also showed the HCW rates paralleled and even preceded wider population trends. 1 …”
Section: Discussionmentioning
confidence: 99%
“… 5 Previous studies have shown the impacts from workplace outbreaks beyond the affected cases to their surrounding community adding to the overall burden of illness from household and community transmission. 3 , 9 Identifying vulnerable industry sectors and their related community transmission is necessary to target public health interventions to prevent outbreaks and subsequent community spread. Our objectives were to: (1) describe workplace outbreaks in Ontario over the first 6 months of 2020 (the first wave of the SARS-CoV-2 pandemic and initial stages of re-opening); (2) describe cases associated with these workplace outbreaks; and (3) estimate the additional burden of illness due to associated household transmission.…”
mentioning
confidence: 99%